Australian Maltreated Infants and Young Children Can Achieve Positive Relational Health With Neurodevelopmentally- and Trauma-Informed Interventions Provided Within Relationally-Positive and Stable Environments - Cox, Allison; Frederico, Margarita; Mosse, Holly; Radford, Lyn; Ambry, Dallas; Ryan, Clare (Frontiers in Psychiatry, 2021)
Background: Childhood maltreatment such as abuse, neglect and family violence has a profound impact on children's psychological and relational functioning and their lifelong trajectory, with associated adverse physical and mental health outcomes, higher mortality rates and reduced socioeconomic opportunities. The aim of the study was to explore the impact of neurodevelopmentally- and trauma-informed interventions on the relational health of children who have experienced maltreatment. Context: The study was conducted at Berry Street Take Two, an Australian therapeutic service. Take Two provides services to Victorian children aged 0-18 years, to address the impact of the trauma they have experienced from maltreatment. Take Two clinicians use relational and ecological frameworks, neurodevelopmental research and evidence-informed approaches to repair family relationships and develop networks of caring adults that focus on meeting the child's needs. Take Two uses the NMT approach as a framework for clinical intervention-planning and is site-certified in the use of the NMT Clinical Practice tools. Method: The mixed methods study had two components. A cross sectional study of baseline and repeat clinical measure data (HoNOSCA and SDQ) with a cohort of children aged 2–11 years (n = 91), who were clients of Berry Street Take Two between 2014 and 2019, was conducted utilizing SPSS. The quantitative data analysis was supplemented by three case studies of Berry Street Take Two clients, which explored the process of intervention, including intervention type, timing and dosage. The case studies drew on the full case record for each child to illustrate the impact of NMT-informed interventions on the relational health, psychological and behavioral functioning of children. Results: The study found that Take Two intervention was associated with improved relational health, measured by the NMT metric and supported by significant positive changes on the SDQ and HoNOSCA with medium effect sizes (cohen's d). The case study analysis highlighted the importance of intervention addressing individual, family and systems elements to bring about positive change. Conclusions: This study illustrates the value of neurodevelopmental trauma-informed interventions in positively impacting on the relational health and current functioning of maltreated children and the potential to reduce the lifelong impact of maltreatment.